ANALISIS STANDAR PENGELOLAAN PENDIDIKAN DALAM MENDUKUNG KEMAJUAN SEKOLAH SMP IT AL MADANI - Amanatulloh, Sahrul Adi; Nugraheni, Ardhina Maya; Sudjono, Sudjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Limited involvement of stakeholders, lack of action plans that are appropriate to the situation and conditions, lack of evaluation and monitoring. This has an impact on the unclear direction and goals of the school. The problem to be researched focuses on the application of educational management standards in planning the school's vision, mission and goals at Al-Madani IT Middle School. The goal that is expected to be achieved in this research is to overcome the above problems in achieving educational management standards at SMP IT Al-Madani Gunung Pati, Semarang City. In this research, the author used qualitative research methods. The research method uses qualitative methods and a descriptive approach. The formulation of the Vision and Mission has not been implemented properly. This is of course a lesson for all parties, especially the leadership of the Foundation Institution, because what was conveyed by the Principal of the School has not been supported or committed between stakeholders so that the information obtained is not in sync between the Foundation Institution and the school, a situation like this cannot continue continuously and it is necessary to planning for more mature management standards is carried out.